The popular asks for passage: Chiquinha Gonzaga and Joaquim Callado on the art of encounter - Oliveira de Freitas, Ricardo; Antunes da Silva, Carolina (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
Brazilian music was born from the meeting of two important figures within the Brazilian music scene: Chiquinha Gonzaga and Joaquim Callado. Both black, transited in the alleys of a Rio de Janeiro in a process of transformation not only political, but, above all, social and structural. From the reforms initiated in the Second Reign and consolidated in the Republic, the social stratification that was already intense, became even more evident. In this way, art begins to act in the service of society as a vector of entertainment, but also of struggle and empowerment. This article, based on a historical analysis, seeks to verify the relationship between Joaquim Callado and, above all, Chiquinha Gonzaga with the society of their times, revealing the way in which the composers used art as an instrument of change.